2008
DOI: 10.1002/er.1392
|View full text |Cite
|
Sign up to set email alerts
|

Modeling an industrial energy system: Perspectives on regional heat cooperation

Abstract: SUMMARYThrough energy efficiency measures, it is possible to reduce heat surplus in the pulp and paper industry. Yet pulp and paper mills situated in countries with a heat demand for residential and commercial buildings for the major part of the year are potential heat suppliers. However, striving to utilize the heat within the mills for efficient energy use could conflict with the delivery of excess heat to a district heating system. As part of a project to optimize a regional energy system, a sulfate pulp mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…MIND is a method for optimisation of dynamic energy systems, based on mixed integer linear programming (MILP) [31]. Areas where MIND has been used include analysis of forest industry [32,33], steel industry [34], and interaction between industries and DH networks [35,36].…”
Section: Optimisation Modelmentioning
confidence: 99%
“…MIND is a method for optimisation of dynamic energy systems, based on mixed integer linear programming (MILP) [31]. Areas where MIND has been used include analysis of forest industry [32,33], steel industry [34], and interaction between industries and DH networks [35,36].…”
Section: Optimisation Modelmentioning
confidence: 99%
“…Process integration methods provide useful tools for evaluating possible process alternatives. Several studies of paper and pulp mills have been carried out by using pinch analysis [1][2][3][4][5][6][7] and mathematical programming [8][9][10][11][12][13]. However, the scope of modelling and simulation has not been as complete as it is in many other process industries.…”
Section: Introductionmentioning
confidence: 99%
“…It was also shown that mixed-integer linear programming (MILP) provides a methodology for determining optimal strategies in order to minimise the overall energy costs in such industries [16]. Studies using such a methodology in a Swedish context include for example [17][18][19][20][21][22][23][24], where MIND (Method for analysis of INDustrial energy systems) was used. MIND is a method developed for optimization of dynamic industrial energy systems [17].…”
Section: Introductionmentioning
confidence: 99%
“…These studies comprise large energy-intensive sites such as Swedish pulp and paper mills and steelworks, e.g. [17][18][19][20][21][22][23][24]. The need to apply the method in other sectors, including small and medium-sized manufacturers such as the Swedish foundry industry, cannot be understated.…”
Section: Introductionmentioning
confidence: 99%